2020
DOI: 10.1002/hipo.23291
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurogenesis and memory in adolescence following intrauterine growth restriction

Abstract: Intrauterine growth restriction (IUGR) is associated with hippocampal alterations that can increase the risk of short‐term memory impairments later in life. Despite the role of hippocampal neurogenesis in learning and memory, research into the long‐lasting impact of IUGR on these processes is limited. We aimed to determine the effects of IUGR on neuronal proliferation, differentiation and morphology, and on memory function at adolescent equivalent age. At embryonic day (E) 18 (term ∼E22), placental insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Dean and colleagues [16] used Rapid-Golgi with Neurolucida to quantify neuronal morphology in a fetal sheep model of cerebral ischemia and show impaired expansion of the dendritic arbor and a significant reduction in spine density following ischemia. Preclinical models of fetal growth restriction have used the Rapid-Golgi method with Im-ageJ (with ImageJ plugins for neuronal morphological analysis) [17,34], showing altered morphology of CA1 pyramidal neurons and a significant reduction in dendritic length [17]. Interestingly, an unexpected increase in spine density was seen in a guinea pig model of fetal growth restriction [17].…”
Section: Discussionmentioning
confidence: 99%
“…Dean and colleagues [16] used Rapid-Golgi with Neurolucida to quantify neuronal morphology in a fetal sheep model of cerebral ischemia and show impaired expansion of the dendritic arbor and a significant reduction in spine density following ischemia. Preclinical models of fetal growth restriction have used the Rapid-Golgi method with Im-ageJ (with ImageJ plugins for neuronal morphological analysis) [17,34], showing altered morphology of CA1 pyramidal neurons and a significant reduction in dendritic length [17]. Interestingly, an unexpected increase in spine density was seen in a guinea pig model of fetal growth restriction [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that fetal growth restriction (also known as intrauterine growth restriction) affects the development of hippocampus and is associated with a decreased hippocampus volume but is also associated with an overall reduced brain volume, abnormalities in the development of white matter myelination and the basal ganglia. 47 , 116 - 122 Moreover, fetal growth restriction has been shown to lead to a reduction in motor capabilities, cognition, and learning as well as behavioral issues such as poor attention and altered mood. 116 - 123 …”
Section: Discussionmentioning
confidence: 99%
“… 47 , 116 - 122 Moreover, fetal growth restriction has been shown to lead to a reduction in motor capabilities, cognition, and learning as well as behavioral issues such as poor attention and altered mood. 116 - 123 …”
Section: Discussionmentioning
confidence: 99%
“…3,4 The essence of IUGR is the adaptive protection of the fetus against insufficient nutrient supply, with the potential of long-term effects on organs such as the lung. 11,28,29 The adverse effects on lung development have been widely addressed in previous studies. 5,6,16 However, there is no specific clinical intervention to prevent MFRinduced pulmonary dysplasia in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is the most common cause of IUGR, with nutritional insufficiency being the most common contributor in developing countries 3,4 . The essence of IUGR is the adaptive protection of the fetus against insufficient nutrient supply, with the potential of long‐term effects on organs such as the lung 11,28,29 . The adverse effects on lung development have been widely addressed in previous studies 5,6,16 .…”
Section: Discussionmentioning
confidence: 99%